Investigation of the Mechanical Behavior of Full-Scale Experimental Bugis-Makassar Timber House Structures - Armin Aryadi; Herman Parung; Rita Irmawaty; Andi A. Amiruddin (Salehan Institute of Higher Education, 2024)
The Sulawesi region is located at the confluence of a smaller Philippine plate and three major global plates, namely the Indo-Australian, Pacific, and Eurasian. This strategic location makes Sulawesi and the surrounding earthquake-prone region in Indonesia. Recognizing the seismic vulnerability of this region, various measures, such as the use of houses on stilts, have been explored to enhance earthquake resistance. These structures are designed to avoid direct exposure to seismic energy, according to several reports on Indonesian earthquakes. In the last two years, an in-depth investigation has been carried out to analyze the behavior and resistance of Bugis Traditional Houses to earthquakes. Although simulation and computational studies are still in progress, the results show that Bugis-Makassar House on stilts maintains an elastic state with a high level of performance. Therefore, this study aimed to investigate the mechanical behavior of Bugis-Makassar stilt house structures using full-scale tests. During the investigation, experimental testing was conducted using house specimens measuring 1.5×2.3 m in the laboratory. A cyclic lateral loading analysis was performed using ISO 16670-2003 as a guide. The results showed that cyclic lateral loads caused house structures to sway, while the timber experienced minimal damage. Both the hysteresis energy, EH to EI, and the energy conversion ratio, GPE to ESE (ER), were found to be approximately balanced. This equilibrium suggested that seismic energy can be cyclically stored and released to reduce damage to structural elements. Doi: 10.28991/CEJ-2024-010-06-04 Full Text: PDF